PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS' INDEPENDENT THINKING (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article reveals the role of national values ​​and the role of encyclopedic scholars in the development of students' ability to think independently.